Ublituximab plus ibrutinib versus ibrutinib alone for patients with relapsed or refractory high-risk chronic lymphocytic leukaemia (GENUINE): a phase 3, multicentre, open-label, randomised trial. Issue 4 (April 2021) - Sharman, Jeff P; Brander, Danielle M; Mato, Anthony R; Ghosh, Nilanjan; Schuster, Stephen J; Kambhampati, Suman; Burke, John M; Lansigan, Frederick; Schreeder, Marshall T; Lunin, Scott D; Zweibach, Alexander; Shtivelband, Mikhail; et al.
Summary: Background: Patients with chronic lymphocytic leukaemia and high-risk features have poorer outcomes on ibrutinib than those without high-risk features. The aim of this study was to assess the benefit of adding ublituximab, an anti-CD20 monoclonal antibody, to ibrutinib therapy in this population. Methods: We did a randomised, phase 3, multicentre study (GENUINE) of patients aged 18 years or older with relapsed or refractory chronic lymphocytic leukaemia with at least one of 17p deletion, 11q deletion, or TP53 mutation, at 119 clinics in the USA and Israel. Eligible patients had received at least one previous chronic lymphocytic leukaemia therapy and had an Eastern Cooperative Oncology Group performance status of 2 or lower. We randomised patients (1:1) using permuted block randomisation with a block size of four and stratified by previous lines of therapy (one vs two or more) to receive ibrutinib alone or ibrutinib in combination with ublituximab. Treatment allocation was not masked to patients or investigators. Ibrutinib was given orally daily at 420 mg for all cycles. Ublituximab was given intravenously in 28-day cycles, with increasing doses during cycle 1 (≤150 mg on day 1, 750 mg on day 2, and 900 mg on days 8 and 15) and continuing at 900 mg on day 1 of cycles 2–6. After cycle 6, ublituximab was given at 900 mg every three cycles. The study was initially designed with co-primary endpoints of progression-free survival and overall response rate but due to protracted patient accrual, the protocol was amended to have a single primary endpoint of independent review committee-assessed overall response rate (defined as the proportion of patients who had a partial response, complete response, or complete response with incomplete marrow recovery according to the 2008 International Workshop on CLL criteria) in the intention-to-treat population. Safety was evaluated in the population of patients who received at least one dose of study treatment. This trial is registered with ClinicalTrials.gov, NCT02301156, and the final analysis is presented. Findings: 224 patients were assessed for eligibility, of whom 126 patients were enrolled and randomly assigned to receive ublituximab plus ibrutinib (n=64) or ibrutinib alone (n=62) between Feb 6, 2015, and Dec 19, 2016. After a median follow-up of 41·6 months (IQR 36·7–47·3), the overall response rate was 53 (83%) of 64 patients in the ublituximab plus ibrutinib group and 40 (65%) of 62 patients in the ibrutinib group (p=0·020). 117 patients, including 59 in the ublituximab plus ibrutinib group and 58 in the ibrutinib group, received at least one dose of treatment and were included in safety analyses. Most adverse events were grade 1 or 2. The most common grade 3 and 4 adverse events were neutropenia (11 [19%] patients in the ublituximab plus ibrutinib group and seven [12%] in the ibrutinib group), anaemia (five [8%] and five [9%]), and diarrhoea (six [10%] and three [5%]). The most common serious adverse events were pneumonia (six [10%] in the ublituximab plus ibrutinib group and four [7%] in the ibrutinib group), atrial fibrillation (four [7%] and one [2%]), sepsis (four [7%] and one [2%]), and febrile neutropenia (three [5%] and one [2%]). Two patients in the ublituximab plus ibrutinib group died due to adverse events (one cardiac arrest and one failure to thrive), neither of which were treatment-related. Five patients in the ibrutinib group died due to adverse events, including one cardiac arrest, one cerebral infarction, one intracranial haemorrhage, one Pneumocystis jirovecii pneumonia infection, and one unexplained death; the death due to cardiac arrest was considered to be treatment-related. Interpretation: The addition of ublituximab to ibrutinib resulted in a statistically higher overall response rate without affecting the safety profile of ibrutinib monotherapy in patients with relapsed or refractory high-risk chronic lymphocytic leukaemia. These findings provide support for the addition of ublituximab to Bruton tyrosine kinase inhibitors for the treatment of these patients. Funding: TG Therapeutics.